ANALISIS SISTEM PENGENDALIAN INTERNAL DALAM PELAKSANAAN PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SMK NEGERI 1 SUNGAI KAKAP - B51112067, M. FAHRUL WAHYUDI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This research aims to identify wheather the implementation of internal control system of the School Operational Assistance (SOA) or (Bantuan Operasional Sekolah, BOS) in the public vocation high school 1 Sungai Kakap (SMK Negeri 1 Sungai Kakap) has been operating effectively or not. The BOS program is an effort to in crease public access, especially students from poor families, of quality education by pursuing the nine-year compulsory education. This research was conducted in the public vocation high school 1 Sungai Kakap. In order to describe the mechanism of the BOS funds distribution that consists of the flow of transmitting student number data, allocation and selection data, and fund distribution data, this research uses three analyses that are the evaluation of the organizational structure, the analysis flowchart explaining the mechanism of distribution of BOS funds and internal control questionnaires. The analyses were used altogether to understand the management of school operational funds (SOA) or (Bantuan Operasional Sekolah, BOS). Based on the results of the analysis, it can be concluded that the implementation of internal control system of the School Operational Assistance (SOA) or (Bantuan Operasional Sekolah, BOS) in the public vocation high school 1 Sungai Kakap is good. It can be seen from the results of the analysis of the organizational structure evaluation, the flowchart, and internal control questionaires showing that the mechanism has been implemented effectively and procedurally. Keywords: internal control system and the School Operational Assistance (Bantuan Operasional Sekolah, BOS). Â